Stone age in the Philippines (Makati Felta Book Sales)
An overview of pre-historic life and culture in the Philippines as characterized by two major periods: Paleolithic or Stone Age 500,000 to 8,000 B.C., and Neolithic or New Stone Age from 8,000 to circa 1,500 B.C. Unearth archaeological finds from two major prehistoric sites in the country: Cagayan Valley and Tabon cave in Palawan.
Keywords: Stone age -- Philippines; Anthropology; Philippines history